Strength of lithium disilicate ceramics bonded with two different adhesives - Pezo-Vargas, Karlla Elizabeth; Salinas-Francia, Joyce Mariana; Domínguez, John Alexis (Revista Facultad de Odontología Universidad de Antioquia, 2022)
Introduction: lithium disilicate ceramics are an excellent choice in rehabilitation, made with the technique of injection or machining. The aim of this study was to evaluate the influence of two adhesive systems on the values of binding resistance in injected and machined lithium disilicate ceramics. Methods: lithium disilicate disks, IPS e. were used Max CAD (Ivoclar Vivadent, Liechtenstein, Swiss), 10mm in diameter and 1mm in thickness embedded in PVC tubes. Was distributed in 4 working groups, 2 in injected lithium ceramics and 2 in machined, Palfique Bond and Tetric N-bond Universal adhesives were applied according to the group distribution, then photopolymerized for 10 seconds with led light bulb, Tygon® tubes were placed for filling with fluid resin; once the Tygon® tubes were removed. The samples were taken to a universal testing machine where the micro-spraying test was performed. Results: the most significant binding resistance values were found in lithium disisilicate ceramics adhered with the Palfique Bond and Tetric Bond adhesive having a significant difference (p= 0,001), the bond strength values of the Palfique Bond and Tetric Bond adhesive in injected ceramic did not differ significantly. Conclusion: machined lithium disilicate ceramics have better values of binding resistance to micro-spraying.